Preparation and bioactivity of apatite coating on Ti6Al4V alloy by microwave assisted aqueous chemical method. Issue 16 (December 2016) - Zhang, Feiyang; Cai, Shu; Xu, Guohua; Wang, Fengwu; Yu, Nian; Ling, Rui; Wu, Xiaodong
Abstract: To improve the bioactivity of titanium and its alloys, dense and uniform apatite coatings were prepared on Ti6Al4V titanium substrates using microwave assisted aqueous chemical method. The influence of the pretreatment to the titanium substrates and the Ca/P molar ratio of the microwave solution on the coating deposition and morphology, as well as the bioactivity of the coated samples were studied. Results showed that during the microwave process, alkali treatment followed by heat treatment to the titanium substrates would promote the rapid deposition of hydroxyapatite to form coating. And the morphologies of the apatite coatings could be adjusted by the Ca/P molar ratio of the microwave solution. After immersion test in simulated body fluid (SBF), the coated titanium alloy exhibits a good bioactivity by inducing the formation of apatite depositions.